Pre-processing of coal combustion fly ash by classification for enrichment of rare earth elements - Christof Lanzerstorfer (Energy Reports, 2018)
Fly ash from the combustion of coal shows potential as a source of valuable metals like the rare earth elements (REEs). These are present in the fly ash at low concentrations. Thus, simple dry pre-processing methods that can produce REE-enriched fractions from the fly ash could improve the feasibility of subsequent extraction processes. The performed air classification experiments with a coal combustion fly ash showed a certain size dependence of the REE concentrations. In the different size fractions the REEs were enriched or depleted. Thereby, the different groups of REEs showed differences in their behavior. In the finest size fraction all REEs were enriched by a factor of 1.05 to 1.65. In contrast, in the coarsest size fraction and in the second finest size fraction all REEs were depleted (0.63 to 0.78 and 0.58 to 0.92). In the medium size fraction the concentrations were close to those in the fly ash and in the second largest size fraction the light REEs (La, Ce, Pr, Nd and Sm) were enriched by a factor of 1.19 to 1.35, while the concentrations of the other REEs were similar as in the fly ash. Thus, air classification shows some potential as a simple dry pre-processing step for the separation of REE-enriched fractions from the bulk of a coal fly ash.
Keywords: 330; Classification; Coal combustion; Fly ash; Particle size; Rare earth elements